Grain Size Sensitive Creep During Simulated Seismic Slip in Nanogranular Fault Gouges: Constraints From Transmission Kikuchi Diffraction (TKD). Issue 10 (24th October 2019) - Demurtas, Matteo; Smith, Steven A. F.; Prior, David J.; Brenker, Frank E.; Di Toro, Giulio
Abstract: Nanograins (≪1 μm) are common in the principal slip zones of natural and experimental faults, but their formation and influence on fault mechanical behavior are poorly understood. We performed transmission Kikuchi diffraction (spatial resolution 20–50 nm) on the principal slip zone of an experimental carbonate gouge (50 wt% calcite, 50 wt% dolomite) that was deformed at a maximum slip rate of 1.2 m/s for 0.4 m displacement. The principal slip zone (PSZ) consists of nanogranular aggregates of calcite, Mg‐calcite, dolomite and periclase, dominated by grain sizes in the range of 100–300 nm. Nanograins in the ultrafine (< 800 nm) PSZ matrix have negligible internal lattice distortion, while grains > 800 nm in size contain subgrains. A weak crystallographic preferred orientation is observed as a clustering of calcite c ‐axes within the PSZ. The high‐resolution microstructural observations from transmission Kikuchi diffraction, in combination with published flow laws for calcite, are compatible with high‐velocity slip in the PSZ having been accommodated by a combination of grain size sensitive creep in the ultrafine matrix, and grain size insensitive creep in the larger grains, with the former process likely controlling the bulk rheology of the PSZ after dynamic weakening. If the activation energy for creep is lowered by the nanogranular nature of the aggregates, this could facilitate grain size sensitive creep at high (coseismic) strain rates and only moderate bulk temperatures of approximately 600 °C, although temperatures up to 1000 °C could be locally achieved due to processes such as flash heating. Key Points: Transmission Kikuchi diffraction performed on an experimental nanogranular slip zone in calcite‐dolomite gouge Slip zone composed mainly of nanograins 200–300 nm in size with low internal lattice distortion. Grains > 800 nm in size have subgrains Grain size sensitive creep controlled the rheology of the slip zone after dynamic weakening at high slip velocity